2018
DOI: 10.2507/ijsimm17(4)441
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Friction Model Performance in a Skew Rolling Process Numerical Simulation

Abstract: This paper studies the influence of diverse friction models on the numerical analysis of an industrial skew rolling mill using FORGE®. The originality of the present contribution is the analysis of the effect of the friction model on important parameters, namely, consumed power, plastic deformation and surface temperature. The aim is to evaluate which of these friction models is appropriate for simulating these industrial processes. The high values of temperature, pressure and sliding velocity at the contacts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…where τ is the shear stress on contact surface, m is the friction factor (set equal to m = 0.8 for the rolls [27] and m = 0.2 for other tools), k is the shear yield stress ( = √3) ⁄ . The model of the material used in the numerical analysis was the 42CrMo4 grade of steel (obtained from the material library database of the program), expressed by the following equation:…”
Section: Materials 2020 13 × For Peer Review 3 Of 21mentioning
confidence: 99%
See 1 more Smart Citation
“…where τ is the shear stress on contact surface, m is the friction factor (set equal to m = 0.8 for the rolls [27] and m = 0.2 for other tools), k is the shear yield stress ( = √3) ⁄ . The model of the material used in the numerical analysis was the 42CrMo4 grade of steel (obtained from the material library database of the program), expressed by the following equation:…”
Section: Materials 2020 13 × For Peer Review 3 Of 21mentioning
confidence: 99%
“…where τ is the shear stress on contact surface, m is the friction factor (set equal to m = 0.8 for the rolls [27] and m = 0.2 for other tools), k is the shear yield stress (k = σ F / √ 3). Thermal effects occurring during forming were considered in the analysis.…”
Section: Materials 2020 13 × For Peer Review 3 Of 21mentioning
confidence: 99%
“…Friction was modelled using the Tresca model, assuming that the friction factor at the material/tool interface was 0.8 [18]. In addition, it was assumed that during the compression the tools had a constant temperature of 50°C and the coefficient of heat transfer between the specimen and tools was 10,000 W/m 2 K.…”
Section: Fem Analysis Of Rotational Compression Between Channel-diesmentioning
confidence: 99%
“…More recent studies are focussed on increasing model accuracy by reducing assumptions on boundary conditions or by reproducing the different phenomena occurring in the RTP process. Murillo-Marrodán et al [14] showed the importance of the correct selection of boundary conditions for the reliability of model results and conclusions. Another aspect that enhances the model accuracy is the correlation of strain.…”
Section: Introductionmentioning
confidence: 99%